Outcomes following calcium channel blocker exposures reported to a poison information center - Mikkel B. Christensen; Kasper M. Petersen; Søren Bøgevig; Salam Al-Gibouri; Espen Jimenez-Solem; Kim P. Dalhoff; Tonny S. Petersen; Jon T. Andersen (BMC, 2018)
Abstract Background Calcium channel blockers (CCBs) are widely used drugs that have a narrow therapeutic index. Even minor overdoses must be treated in-hospital due to the risk of severe hypotension and bradycardia. We aimed to describe trends in CCB use and overdoses in Denmark. Methods Data on enquiries concerning CCBs reported to the Danish Poisons Information Center (DPIC) from January 2009 to January 2015 was coupled with data on hospitalization and mortality obtained from Danish National Registers. We obtained data on the general use of CCBs in Denmark and retrieved medical charts on fatal cases. Results From a total of 126,987 enquiries to the DPIC in 2009-2014 we identified 339 CCB unique exposures (3‰ of all). Children < 5 years accounted for 20% all exposures and these were classified as 'intake during playing' (61%) and 'medication errors' (39%). Among adults 'suicidal poisonings' (58%), and 'medication errors' (34%) were most frequent. A majority (81%) of exposures led to hospital admission. Seven patients (2%) died from the CCB exposure and all were adults with 'suicidal poisoning'. Amlodipine accounted for 95% of all CCB prescriptions, was involved in 71% of enquiries and in 29% of fatalities. Verapamil accounted for 3% of prescriptions, was involved in 13% of enquiries and 57% of fatalities. Conclusion Four fifths of enquiries to the DPIC result in hospitalization and one fifth concern small children. Mortality were infrequent and occurred only in adults with suicidal exposures and with and an overrepresentation of verapamil exposures.